Penggunaan Model Pembelajaran Knisley Berbasis Kontruktivisme dalam Meningkatkan Self Confidence Mahasiswa - Sari, Maila; Oktafia, Mesi (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2024)
Mathematics education plays a crucial role in the cognitive and affective development of students, including self-confidence in understanding the material. This study aims to evaluate the impact of the Knisley learning model based on constructivism on students' self-confidence. The Knisley learning model provides direct experiences, group collaboration, and individual reflection, which is presumed to enhance students' self-confidence in mathematics learning. This research employs a quantitative approach with an experimental design. The study population consists of 34 fourth-semester students from IAIN Tadris Matematika, divided into two groups: experimental and control. The instrument used in this study is a self-confidence questionnaire. Data collected from the questionnaires distributed to both groups were analyzed to determine the difference in average self-confidence scores between the experimental group using the Knisley constructivism-based model and the control group not using this model. The results indicate that the experimental group had a higher average self-confidence score (45.52) compared to the control group (61.05). The significant value obtained from SPSS testing is 0.0000, which is smaller than the significance level (α = 0.05), indicating that H1 is accepted. Therefore, it can be concluded that students' self-confidence using the Knisley constructivism-based learning model is better than that of students not using the Knisley model, meaning there is an effect of implementing the Knisley constructivism-based learning model on the self-confidence of Tadris Mathematics students. The Knisley constructivism-based model in mathematics learning provides relevant learning contexts, encourages active interaction, and facilitates reflection that supports the development of self-confidence. Thus, the application of this learning model has proven to be effective in enhancing students' self-confidence in mathematics learning.